The Effect Of Foodizz Class Training On Improving MSME Performance - Salsabilla, Mesya; Ghia Ghaida Kanita; Mira Nurfitriya (Jurnal Ekonomi, 2024)
Micro, Small, and Medium Enterprises (UMKM) play a strategic role in Indonesia's economic development. However, several challenges hinder their business growth, including business performance among UMKM actors. This study aims to provide a general overview of the training at Foodizz and to assess its impact on the performance of UMKM actors. The research employs a quantitative method with a descriptive and verificative approach, allowing the verification of whether the proposed hypothesis is accepted or not. This study involves 32 participants who attended the "Building a Culinary Business from Scratch" training program organized by Foodizz. Data collection was carried out by distributing questionnaires to the respondents. This research's sources and types of data involve primary data obtained through questionnaires distributed to all participants. The data analysis was conducted using various statistical techniques, including validity tests, reliability tests, classical assumption tests, simple linear regression analysis, t-tests, and the coefficient of determination, utilizing SPSS version 26. The study results show that the training program has successfully achieved its objectives. Participants demonstrated readiness to develop new ideas and a high motivation to grow their businesses. The analysis revealed that 59.2% of the variation in business performance is influenced by the training provided. At the same time, other factors, such as technology and social elements outside the scope of this study, account for 41.8%. This underscores the need for more focused and tailored training programs to meet the specific needs of UMKM and the importance of updating training programs in line with industry developments and challenges.